Chief customer officer 2.0 : how to build your customer-driven growth engine - Bliss, Jeanne (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
The author shares tools and leadership 'recipe cards' for leading and enabling business transformation. This book provides guidance on how to embed competencies into how a company develops products, goes to market, enables and rewards people, and conducts annual planning.
Chief customer officer role clarity -- Unite leadership to achieve customer-driven growth -- Competency one : honor and manage customers as assets -- Competency two : align around experience -- Competency three : build a customer listening path -- Competency four : proactive experience reliability & innovation -- Competency five : one-company leadership, accountability, and culture -- Staging the work -- Establishing and filling the chief customer officer role.
Includes index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Customer relations -- Management; Industrial management; Gestion d'entreprise.; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Customer relations -- Management; Industrial management